The impact of land reform on the development of land relations in Ukraine - Avramchuk, B. O. (Land Management, Cadastre and Land Monitoring, 2017)
Reviewed the influence of the major steps, that have been taken to ensure the imple‐ mentation of the basic objectives of land reform, on the development of land relations in Ukraine, conducted their analysis and shows major shortcomings in carrying out land reform.